2014
DOI: 10.1103/physreva.89.052117
|View full text |Cite
|
Sign up to set email alerts
|

Quantum limits on postselected, probabilistic quantum metrology

Abstract: Probabilistic metrology attempts to improve parameter estimation by occasionally reporting an excellent estimate and the rest of the time either guessing or doing nothing at all. Here we show that probabilistic metrology can never improve quantum limits on estimation of a single parameter, both on average and asymptotically in number of trials, if performance is judged relative to mean-square estimation error. We extend the result by showing that for a finite number of trials, the probability of obtaining bett… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
118
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(124 citation statements)
references
References 44 publications
6
118
0
Order By: Relevance
“…Especially for the latter, a post-selection of the measurement results is involved and the role played by post-selection in quantum metrology has attracted a lot of attention recently [68][69][70][71][72]. Mixed-state cloning or broadcasting would be also very interesting in terms of QFI [20].…”
Section: Discussionmentioning
confidence: 99%
“…Especially for the latter, a post-selection of the measurement results is involved and the role played by post-selection in quantum metrology has attracted a lot of attention recently [68][69][70][71][72]. Mixed-state cloning or broadcasting would be also very interesting in terms of QFI [20].…”
Section: Discussionmentioning
confidence: 99%
“…However, unless there is a severe mismatch between the quality of detection in the two variables, imaginary weak values will not provide a signi cant advantage [12]. On the other hand, when case 2 is compared to case 3 in Figure 1, then postselection is merely data rejection, which cannot improve estimation under the most general evolution allowed by quantum theory [17]. This latter analysis therefore covers experiments involving any dened quantities, including imaginary and even complex weak values.…”
Section: Imaginary Weak Valuesmentioning
confidence: 99%
“…This fact has motivated a long standing feeling that weak-value ampli cation can help to overcome such problems. However, we have shown that estimation inequalities analogous to (4) hold in the presence of a broad class of noise before, during, and after the weak measurement [12,16,17,21]. Together these articles treat the most prevalent types of noise (including pixelation, detector jitter, and dephasing), and a similar approach can be used to analyse other imperfections.…”
Section: Technical Noisementioning
confidence: 99%
See 2 more Smart Citations